Myocardial Perfusion Imaging in the Evaluation of Outcome of Coronary Intervention in Coronary Artery Disease Patients (Bangladesh Journal of Nuclear Medicine, 2019)
Background: Coronary artery disease (CAD) is an important medical and public health issue because it is one of the leading causes of death and disability throughout the world and is rapidly emerging as a major cause of mortality in developing countries including Bangladesh. SPECT-MPI is a cost- effective and non invasive means of identifying ischemic and viable myocardium along with its vascular distribution. This study is aimed to evaluate prospectively the ability of MPI to predict the outcome of Coronary Intervention in CAD patients of Bangladesh who are referred to National Institute of Nuclear Medicine & Allied Sciences (NINMAS) for performing MPI.Patients and Methods: This prospective longitudinal and observational type of study was carried out in National Institute of Nuclear Medicine & Allied Sciences (NINMAS) located at Bangabandhu Sheikh Mujib Medical University (BSMMU) campus, from July 2017 to June 2018with 12 CAD patients who were referred here. Gated SPECT MPI was performed on the selected patients before any coronary intervention to predict myocardial viability & probable outcome of intervention. A follow up MPI of the same patients was performed after minimum 3 to 4 months of  revascularization procedure to determine the outcome of intervention and to detect in stent restenosis or new onset ischemia if present which can be prevented by additional revascularization procedure. Finally pre and post intervention MPI results were analyzed by standard statistical analysis by using the Statistical Package for Social Sciences version 20.0 for Windows (SPSS Inc., Chicago, Illinois, USA). P values